Estimation of crown competition factor for hybrid walnut (Juglans x intermedia) Mj209xRa planted forests in Spain - Jesus Fernandez-Moya (Annals of Silvicultural Research, 2020)
Many walnut (Juglans spp.) planted forests oriented for timber production have been established during the last decades. These plantations usually have a relatively low initial density (250-400 trees ha-1) and 1 or 2 thinnings are needed for valuable timber production (75-150 trees ha-1 for final harvesting). Hence, forest managers need to design when to perform the thinnings and how to do it. Analyzing the trees crown area is a very helpful and easy-to-use tool to evaluate the competence between trees and design the thinnings. The present study proposes two statistical models to estimate Crown Diameter (CD) and Crown Competence Factor (CCF) as a function of Diameter at Breast Height (DBH) for hybrid walnut (Juglans x intermedia) Mj209xRa planted forests, within a DBH range between 5 cm (min) and 33 cm (max). CD and DBH were measured in 702 trees at the Bosques Naturales SA walnut planted forests in Cuenca, Girona and A Coruña (Spain). The CCF model is a tool to evaluate the Crown Competition Factor as a function of measured DBH in a plantation, and, accordingly, decide if a thinning should be done or not yet and design it.